Peculiarities of Creating Computer Lexicography - Jumalieva, Gulira; Bektenova, Raushan; Haskova, Alena; Gadušová, Zdenka; Kabaeva, Gulnara; Kyrgyzbayev, Aziz (Journal of Education Culture and Society, 2024)
Aim. Purpose of the presented research work is to study nuances of creating computer lexicography, taking into account both modern technological advances and linguistic principles. Methods. To achieve the stated goal, a comprehensive review of existing methodologies and approaches used in creating lexicographic resources was conducted. Additionally, also the problems related to the automation of the process of compiling and updating lexical data were studied. The research methodology included an analysis of modern software tools widely used lexicographic practice, as well as a thorough study of their advantages and limitations. Subsequently a comparative analysis of natural language processing techniques used in the creation of lexicographic databases was conducted. Results. Within the course of the study, there were identified key issues such as accuracy, completeness, data relevance, and the ability to automate update processes. Conclusion. Following the achieved findings, recommendations aimed at optimizing the creation and maintenance of lexicographic resources by integrating modern technologies and language processing techniques were formulated. The authors conclude by emphasizing the importance of improving the methodology of computer lexicography to effectively provide users with up-to-date and reliable linguistic information under the conditions of rapid development of digital technologies.